2014
DOI: 10.1007/s00248-014-0523-1
|View full text |Cite
|
Sign up to set email alerts
|

Parent Material and Vegetation Influence Soil Microbial Community Structure Following 30-Years of Rock Weathering and Pedogenesis

Abstract: The process of pedogenesis and the development of biological communities during primary succession begin on recently exposed mineral surfaces. Following 30 years of surface exposure of reclaimed surface mining sites (Appalachian Mountains, USA), it was hypothesized that microbial communities would differ between sandstone and siltstone parent materials and to a lesser extent between vegetation types. Microbial community composition was examined by targeting bacterial and archaeal (16S ribosomal RNA (rRNA)) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 72 publications
(83 reference statements)
0
12
1
Order By: Relevance
“…Dimitriu et al (2010) showed that reclamation-mediated effects on microbial properties are mainly attributable to changes in abiotic properties such as soil pH; however, the composition of soil bacterial and fungal communities in forest soil is largely determined by dominant trees (Urbanová et al, 2015). Both parent material (sandstone and siltstone) and nutrient addition (including nitrogen and phosphorus fertilization) affected the rate of succession because of the differences in resource availability (Knelman et al, 2014;Yarwood et al, 2015). In severely degraded soil, microbial community structure and generation were mediated by soil aggregation via the protection afforded by soil organic carbon (Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimitriu et al (2010) showed that reclamation-mediated effects on microbial properties are mainly attributable to changes in abiotic properties such as soil pH; however, the composition of soil bacterial and fungal communities in forest soil is largely determined by dominant trees (Urbanová et al, 2015). Both parent material (sandstone and siltstone) and nutrient addition (including nitrogen and phosphorus fertilization) affected the rate of succession because of the differences in resource availability (Knelman et al, 2014;Yarwood et al, 2015). In severely degraded soil, microbial community structure and generation were mediated by soil aggregation via the protection afforded by soil organic carbon (Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Soil factors and vegetation are important determinants of microbial community composition and could determine the trajectory of ecosystem development (Yarwood et al, 2015). Dimitriu et al (2010) showed that reclamation-mediated effects on microbial properties are mainly attributable to changes in abiotic properties such as soil pH; however, the composition of soil bacterial and fungal communities in forest soil is largely determined by dominant trees (Urbanová et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, parent material and vegetation type interacted to affect soil macroaggregate 84 size, and both factors also shaped microbial community structure following 30 years of 85 surface exposure of reclaimed surface mining sites (Yarwood et al, 2015). The degree to 86 which this occurs with the iconic giant sequoia, however, remains unknown.…”
Section: Introduction 25mentioning
confidence: 99%
“…The spontaneous succession of plant communities in quarries with various substrates has been studied in sufficient detail. Much of the research is devoted to various aspects of succession of the vegetation cover (Kopceva 2005, Neshataev et al 2012, Sumina 2013, the processes of pedogenesis have been analyzed quite thoroughly (Abakumov et al 2013, Yarwood et al 2015. However, complex observations on the restoration of the soil and vegetation cover and the connection of these components remain small.…”
Section: Introductionmentioning
confidence: 99%